Sugar plum spies ebook - Estep, Jennifer (Section 47, 2022)
New York Times bestselling author Jennifer Estep serves up an action-packed holiday adventure in her Section 47 urban-fantasy world of secrets, lies, and superspies with amazing magical abilities. Perfect for fans of Alias, Die Hard, James Bond, Jason Bourne, Nikita, True Lies, and Netflix's Bodyguard. VISIONS OF SUGAR PLUMS . . . Most spies take a break for the holidays, but not me, Charlotte Locke. As an analyst for Section 47, a secret spy organization, I normally use my magical form of synesthesia to uncover lies and track paramortal bad guys from the comfort of my cubicle. But tonight I'm going out into the field, along with my partner, Desmond Percy, a powerful galvanist. Instead of enjoying Christmastime in the city, I'm in a German castle, dressed like a toy soldier and masquerading as a waitress at a swanky Christmas Eve party. My mission? To gather information that will help Section 47 track down a dangerous enemy. Despite the glitz and glamour, I can't shake the sense that something is wrong—and that Desmond and I might not leave the party alive. DANCES OF DEATH . . . My name is Desmond Percy, although I've had many aliases during my years working as a cleaner for Section 47. But I've never had a real partner until Charlotte Locke. My part of the mission is simple: pretend to be a guest and keep an eye on things at the party while Charlotte uses her synesthesia to track down the information we need. But what starts out as a sugar plum dream quickly turns into a holiday nightmare. Forget the mission. All I want for Christmas is to keep Charlotte safe. Note: Sugar Plum Spies is a 47,000-word book. It is book 2 in the Section 47 series, but it can also be read as a stand-alone holiday adventure.